Psychopathological symptoms associated with psychosocial functioning in children and adolescents with autism spectrum disorders and their typically developing peers. (October 2022) - Lassen, Jonathan; Aggernæs, Bodil; Foldager, Malene; Pedersen, Jesper; Oranje, Bob; Kjær, Troels W.; Arnfred, Sidse; Vestergaard, Martin
Abstract: Children and adolescents with autism have increased prevalence of psychosocial disabilities. Studies in autism indicate that key psychosocial factors including adaptive functioning, school absence, special needs education, frequency of peer socialization and participation in organized leisure activities may differ in their relationship with autistic, internalizing and externalizing symptoms, but the findings are so far mixed. Therefore, we examined if these measures of psychosocial functioning displayed specific associations with autistic, internalizing and/or externalizing symptoms in 61 children with autism aged 7–14 years compared to 61 typically developing controls. Multiple linear regression analyses across all participants showed that lower adaptive functioning, frequency of peer socialization and participation in leisure activities were driven by more social communication problems and not internalizing, externalizing or autistic-like symptoms including rigidity, stereotypy and sensory sensitivity. Notably, increased school absence was specifically driven by more internalizing symptoms and not autistic or externalizing symptoms. These associations were observed across all participants, both children with autism and their typically developing peers, and therefore appear to be dimensional and general in nature. Within the autism group, children who received special needs education displayed fewer social communication problems compared to those who attended regular education, while a developmental history of social interaction problems was related to lower adaptive functioning. Our findings suggest that social communication problems are more critical for psychosocial functioning than other autistic-like behaviors, internalizing or externalizing symptoms but that efforts to reduce school absence specifically need to target internalizing symptoms and not autistic-like or externalizing symptoms. Highlights: Developmental history of social problems relates to less adaptive skills in autism. Social Communication problems in autism are related to less peer socialization. Social problems relate to maladaptive functioning in autistic children and controls. Internalization is related to school absence in children with autism and controls. Children with autism receiving special needs education have less autistic symptoms.